Implementation of Character Education Policy by the Sukabumi City Education and Culture Office in Shaping Student Morals and Ethics (Study on the Basic Education Level of Sukabumi City) - Ikang Afrizal; Tuah Nur; Andi Mulyadi (Department of Government Studies, Faculty of Social and Political Sciences, Universitas Syiah Kuala, 2026)
The increasing moral and ethical degradation among younger generations, reflected in the rising cases of bullying and juvenile delinquency, highlights the need for a systematic and sustainable character education policy starting from the elementary education level. This study aims to analyze the implementation of the character education policy by the Department of Education and Culture of Sukabumi City and to identify the factors that support and hinder its implementation. The research employed a qualitative approach using a case study method. Data were collected through in-depth interviews with officials from the Department of Education, school principals, and teachers, supported by observations and document analysis. The findings reveal that character education has been integrated into the curriculum through local wisdom values and various school habituation activities, particularly those with religious orientations. However, its implementation still faces several challenges, including differences in teachers’ understanding of character value internalization, limited supporting facilities, and the suboptimal involvement of families in the character-building process. Therefore, strengthening teachers’ capacity and fostering closer collaboration among schools, families, and the community are essential to improve the effectiveness of the policy.